43‐2: Development of Zero‐bezel Display Utilizing a Waveguide Image Transformation Element. Issue 1 (May 2017) - Lee, Sejin; Moon, Jeongmin; Yang, SeungSoo; Rhim, Jusang; Kim, Bora; Lee, YongSeok; Han, SeungJun; Yoon, SooYoung; Kang, InByeong
Abstract : In this study, we have developed an image transforming optical element which realized a zero‐bezel flat panel display module. The zero‐bezel display module worked not only at the front view but also did at the oblique view, so that omnidirectional image expression was achieved. In addition, resolution of the display was not degraded after addition of the optical element because the resolution of the image transformation element was higher enough to deliver the image with the original resolution. This achievement can be used for a modular unit of a seamless multi‐vision display.